Human MAP Tau Based Targeted Cytolytic Fusion Proteins - Olusiji A. Akinrinmade; Sandra Jordaan; Dmitrij Hristodorov; Radoslav Mladenov; Neelakshi Mungra; Shivan Chetty; Stefan Barth (Biomedicines, 2017)
Some of the most promising small molecule toxins used to generate antibody drug conjugates (ADCs) include anti-mitotic agents (e.g., auristatin and its derivatives) which are designed to attack cancerous cells at their most vulnerable state during mitosis. We were interested in identifying a human cystostatic protein eventually showing comparable activities and allowing the generation of corresponding targeted fully human cytolytic fusion proteins. Recently, we identified the human microtubule associated protein tau (MAP tau), which binds specifically to tubulin and modulates the stability of microtubules, thereby blocking mitosis and presumably vesicular transport. By binding and stabilizing polymerized microtubule filaments, MAP tau-based fusion proteins skew microtubule dynamics towards cell cycle arrest and apoptosis. This biological activity makes rapidly proliferating cells (e.g., cancer and inflammatory cells) an excellent target for MAP tau-based targeted treatments. Their superior selectivity for proliferating cells confers additional selectivity towards upregulated tumor-associated antigens at their surface, thereby preventing off-target related toxicity against normal cells bearing tumor-associated antigens at physiologically normal to low levels. In this review, we highlight recent findings on MAP tau-based targeted cytolytic fusion proteins reported in preclinical immunotherapeutic studies.